New Insights into the Roles of Endolysosomal Cathepsins in the Pathogenesis of Alzheimer's Disease: Cathepsin Inhibitors as Potential Therapeutics - Haque, Azizul; Banik, Naren L.; Ray, Swapan K. (CNS & Neurological Disorders - Drug Targets, 2008)
Endolysosomal proteases such as cysteinyl and aspartyl cathepsins play diverse roles in inflammatory autoimmune diseases, cancers, and neurodegenerative diseases. Cysteinyl cathepsin B and aspartyl cathepsin D levels are markedly elevated in a variety of neurological disorders including Alzheimer's disease (AD), a leading cause of dementia in the elderly. Studies have also shown an increased cathepsin activity in AD patients where senile plaques and neuronal loss are marked features of the disease. Senile plaques contain amyloid-beta (Aβ) peptide, which is produced by proteolytic cleavage of the amyloid precursor protein (APP) by the proteases. In this article, we present the current knowledge of cysteinyl and aspartyl cathepsins in cellular and molecular events that lead to formation of senile plaques in AD. This article also focused on the role of cathepsin inhibitors as disease-modifying treatment strategies that could halt, or even prevent, this devastating neurological disorder.
Keywords: neurodegeneration